Certain Aspects of Mast Cell Carboxypeptidase A3 Involvement in the Pathogenesis of COVID-19 - A. V. Budnevskiy; S. N. Avdeev; E. S. Ovsyannikov; N. G. Alekseeva; V. V. Shishkina; I. A. Savushkina; I. M. Perveeva; V. R. Drobysheva (Туберкулез и болезни лёгких)
The objective: to determine the involvement of lung mast cell carboxypeptidase A3 (SPA3) in the pathogenesis of COVID-19. Subjects and Methods. Samples of autopsy specimens from the lungs of patients who died of severe COVID-19 and patients who died of external causes were examined. On day 2 after the patient's death, the autopsy was performed and autopsy specimens were collected. Histological samples were prepared to analyze the degranulation activity of CPA3-positive mast cells (MCs). Correlations between protease profile and clinical and laboratory parameters were analyzed.Results. In the patients died of COVID-19, the total numbers of CPA3-positive MCs, CPA3-positive MCs with signs of degranulation, and coadjacent CPA3-positive MCs (two CPA3-positive MCs sharing a common cytoplasm) were statistically significantly higher versus the patients from Control Group. Positive correlations were established between the total number of CPA3-positive MCs and CPA3-positive MCs with signs of degranulation with blood hemoglobin level (r = 0.491; p = 0.008; r = 0.521; p = 0.004), between the total number of CPA3-positive MCs degranulating CPA3-positive MCs and adjacent CPA3-positive MCs with total blood protein (r = 0.431, p = 0.020; r = 0.449, p = 0.015; r = 0.456, p = 0.013), and between CPA3-positive MCs with signs of degranulation and total number of CPA3-positive MCs with aPTT level (r = 0.428; p = 0.021; r = 0.374; p = 0.045). Negative correlations were established between the total number of CPA3-positive MCs and the level of INR (r = 0.812; p = 0.050), separately lying CPA3-positive MCs with the number of monocytes (r = 0.384; p = 0.044), jointly adjacent CPA3-positive Mcs with blood eosinophils (r = 0.420, p = 0.023).